2016
DOI: 10.1111/jocn.13270
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying among nurses and their related factors in Japan: a cross‐sectional survey

Abstract: Nurse managers' leadership may influence nurses' workplace bullying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 35 publications
6
61
2
1
Order By: Relevance
“…In total, 19 different organisational antecedents were found across the 22 studies. Organisational factors such as labour environment (i.e., working conditions, tasks and teamwork) and demographics (Ariza‐Montes, Muniz, Montero‐Simó, & Araque‐Padilla, ); workplace environmental factors (i.e., nursing role in quality of care/hospital affairs, staffing resources, and manager's ability); practice environment (Yokoyama et al., ) and organisational culture (An & Kang, ; Yeun & Han, ) are important constructs for understanding incidents of HV. The most relevant constructs used to explore organisational antecedent factors were categorized as influential working conditions, relational aspects of teams and leadership, organisational culture, climate, and the role of structural processes (see Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 19 different organisational antecedents were found across the 22 studies. Organisational factors such as labour environment (i.e., working conditions, tasks and teamwork) and demographics (Ariza‐Montes, Muniz, Montero‐Simó, & Araque‐Padilla, ); workplace environmental factors (i.e., nursing role in quality of care/hospital affairs, staffing resources, and manager's ability); practice environment (Yokoyama et al., ) and organisational culture (An & Kang, ; Yeun & Han, ) are important constructs for understanding incidents of HV. The most relevant constructs used to explore organisational antecedent factors were categorized as influential working conditions, relational aspects of teams and leadership, organisational culture, climate, and the role of structural processes (see Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of humane behaviours is also captured through concepts in collegial work teams (An & Kang, ; Yeun & Han, ). However, studies indicate that team behaviours are also being observed to help younger nurses adapt to organisational norms (i.e., bullying of younger nurses) and, at the same time, they are monitored by nurse managers for signs of HV behaviours (Boateng & Adams, ; Kvas & Seljuk, ; Leiter, Price, & Laschinger, ; Lewis, ; Yokoyama et al., ). Purpora and Blegen () used theoretical concepts to create a mediation model highlighting the importance of peer relationship and job satisfaction in relation to HV; a significant finding was a statistically negative relationship between peer relationship and HV (r = −.641; p < .01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research indicates that the presence of supportive leadership is a key factor in determining whether workplace bullying will occur (Laschinger, Wong, & Grau, ; Yokoyama et al, ). However, nursing unit managers have reported that even when they want to support targets of bullying, they do not always know how to intervene (Johnson, Boutain, Tsai, Beaton, & de Castro, ; Lindy & Schaefer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Current research indicates that the presence of supportive leadership is a key factor in determining whether workplace bullying will occur (Laschinger, Wong, & Grau, 2012;Yokoyama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%